Mitochondrial pyruvate carrier regulates the lignocellulosic decomposition rate through metabolism in Ganoderma lucidum. Issue 14 (6th July 2021) - Xu, Wenzhao; Fan, Junpei; Wang, Yihong; Wang, Yunxiao; Zhu, Jing; Ren, Ang; Yu, Hanshou; Shi, Liang; Zhao, Mingwen
ABSTRACT: The activity of mitochondrial pyruvate carrier (MPC) can be modulated to regulate intracellular metabolism under different culture conditions. In Ganoderma lucidum, the role of MPC in regulating carbon sources remains unknown. By knocking down MPC genes ( MPC1 and MPC2 ), this research found that the loss of MPC increased the growth rate of G. lucidum by 30% in a medium with wood chips as a carbon source. Then cellulase and laccase activities were tested. Endoglucanase and laccase activity increased by 50% and 35%, respectively, in MPC knockdown mutants compared with that in the wild type strain. Finally, the expression levels of genes related to glycolysis were assayed, and the transcription levels of these enzymes were found to be increased by 250% compared with the wild type strain. In conclusion, the regulation of intracellular metabolism by MPC provides a new way to improve the use of nondominant carbon sources such as lignocellulose. Abstract : The impact of the mitochondrial pyruvate carrier on the decomposition of lignocellulose in Ganoderma lucidum is studied.